The development of organization capabilities : Jason Associates' case study - Monteiro, Mariana Pardal (2011)
Comprehending the foundations of firms‟ competitive advantage is a theme that has received general attention as a main area of study in the field of strategic management. Along with old and new suggestions in this topic, two concepts that have been receiving increasing consideration of the researches are the Resource-Based View (RBV) and Dynamic Capabilities (DC). RBV has highlighted that by organizing critical resources companies can gain competitive advantage. This theory has an essential focus in the internal context of the firm. Contrarily, Dynamic Capabilities introduced the external dimension to the company: the environment where it operates. Dynamic Capabilities can be described as a company's capacity to build, integrate and reconfigure both internal and external competences to efficiently manage the alterations in the environment. The research problem involved in this dissertation lies in analyzing how Jason Associates, a HR Consulting Company operating in a moderately dynamic environment, had created the capabilities that allowed it to achieve a competitive advantage. To answer the research question the case study method was adopted. After identifying a total of two capabilities we tested to what extent each capability passes the VRIO criteria (Barney, 1997) and then intending to analyze the company in an external dimension the four dimensions of DCs suggested by Barreto (2010) were applied to the case. This study helps to better understand the relationship between a firm‟s resources and its competitive advantage. Furthermore, this case study also analysis the company in its external conditions, namely to identify how the firm is propense to sense opportunities and seize threats in the market.